1974
DOI: 10.1111/j.1365-2621.1974.tb01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on bovine 1. dorsi muscle of conventional and microwave heating

Abstract: A sequence of adjacent samples of beef 1. dorsi muscle were alternately exposed either to conventional heating for periods of 0-70min at temperatures between 45" and 90°C or to microwaves at a frequency of 2450 MHz for periods of 0-10 sec at power levels between 131 and 1050 W. Protein denaturation was assessed by measuring nitrogen distribution between sarcoplasmic and crude myofibrillar fractions and by electrophoresis ; and concomitant superficial changes in free water and plasticity measured.The attainment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Lyon and Lyon () reported that juiciness in broiler breast meat was also significantly lower for the WC method than for the MW method. Microwave cooking may denature the proteins differently from more conventional cooking due to the time of heat exposure and the heat penetration patterns (Roberts and Lawrie ), and the manner in which moisture is held by proteins in the meat system may differ (Lyon and Lyon ). In this study, samples were cooked using the WC method for 23 min, whereas samples were cooked for 19 min for the OB method.…”
Section: Resultsmentioning
confidence: 99%
“…Lyon and Lyon () reported that juiciness in broiler breast meat was also significantly lower for the WC method than for the MW method. Microwave cooking may denature the proteins differently from more conventional cooking due to the time of heat exposure and the heat penetration patterns (Roberts and Lawrie ), and the manner in which moisture is held by proteins in the meat system may differ (Lyon and Lyon ). In this study, samples were cooked using the WC method for 23 min, whereas samples were cooked for 19 min for the OB method.…”
Section: Resultsmentioning
confidence: 99%
“…As the microwave time extended, the shear force increased significantly (p <.05) among same power setting groups. This may due to less denaturation of the myofibrillar and sarcoplasmic proteins (Roberts and Lawrie 2007). All microwave cooked yak meats had significantly lower shear force compared to water bath cooked (p <.05) except for samples processed by low power for 100 s and this inferred that the tenderness of cooked yak meat had been improved with microwave cooking.…”
Section: Shear Forcementioning
confidence: 90%
“…Microwave cooking has been applied for studying the influence on quality of various raw meat (Conchillo et al 2005;Roberts and Lawrie 2010;Chen et al 2015;Liu et al 2018). Nevertheless, research on yak processed meat products by microwave heating technology has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This is a temperature range which the myofibrillar proteins coagulate and it corresponds to the first phase of toughness reported by Davey and Gilbert as above. Following heat denaturation of proteins, the myofibrillar network tightens which results in the release of meat juices (Hamm, 1960) and rigidity of tissue (Robert and Lawrie, 1974).…”
Section: Tenderness and Juicinessmentioning
confidence: 99%